A highly efficient designer cell for enantioselective reduction of ketones. Issue 1 (26th September 2014) - Srivastava, Gautam; Pal, Mohan; Kaur, Suneet; Jolly, Ravinder S.
Abstract : A highly efficient designer cell, surf-crs-gdh, which coexpresses carbonyl reductase (crs) and glucose dehydrogenase (gdh) on the cell surface, has been constructed and its enzyme activities were compared with those of the corresponding cell, cyto-crs-gdh, which coexpresses crs and gdh in cytoplasm. Abstract : A designer cell, surf-crs-gdh, coexpressing carbonyl reductase (crs) and glucose dehydrogenase (gdh) on the cell surface has been constructed and its enzyme activities are compared with those of the corresponding cell, cyto-crs-gdh, coexpressing crs and gdh in cytosol. For various ketones, surf-crs-gdh exhibited 48- to 265-fold higher crs activity per unit protein compared to cyto-crs-gdh.